Byzantine Weaponry and Military Equipment in the Homilies of St Gregory of Nazianzus (Paris, Gr. 510) - Valeri Yotov (Fasciculi Archaeologiae Historicae)
The author discusses illustrations presenting weaponry and military equipment in the famous manuscript of „The Homilies of St. Gregory of Nazianzus” (Paris, Bibliothèque Nationale, MS Gr. 510), completed in Constantinople in 879-882. Shields are usually of round or oval shapes. Basically, they are painted in red and much more rarely in blue. They are outlined by golden or blue stripes. Their decoration is difficult to determine but some geometric forms and simple wavy lines or vine branches can be seen. Shields of infantry soldiers are larger, with a diameter of about 1.00 m, while these of cavalry are smaller – about 0.50 m. With regard to swords, the author concludes that in some miniatures in the Homilies there are close parallels to already established type of Byzantine swords named „Garabonc Type” (five examples, dated to the 2nd half of the 9th c.). As regards images of stirrups in the Homilies, the author assumes that stirrups of a triangular shape – so-called Magyars stirrups, were familiar to masters of Byzantine miniatures. Additionally, arms and military equipment depicted in the Homilies offer support in determining some finds of weaponry which have been discovered either during regular excavations or incidentally.